Tube Feedings and Persistent Vegetative State Patients: Ordinary or Extraordinary Means? - Clark, Peter (Christian bioethics, 2006)
This article looks at the late John Paul II's allocution on artificial nutrition and hydration (ANH) and the implications his statement will have on the ordinary-extraordinary care distinction. The purpose of this article is threefold: first, to examine the medical condition of a persistent vegetative state (PVS); second, to examine and analyze the Catholic Church's tradition on the ordinary-extraordinary means distinction; and third, to analyze the ethics behind the pope's recent allocution in regards to PVS patients as a matter of conscience. Rather than providing clarification, I argue that the papal allocution has raised many difficult questions. People in situations where decisions must be made about withdrawal or continued ANH are in need of guidance. Moreover, additional analysis is needed to determine whether the papal allocution is in conflict with the traditional Catholic medical ethics understanding of the ordinary-extraordinary care distinction.